Edukacja medialna w szkolnych programach nauczania w Anglii i Niemczech - Ławniczak, Joanna (Wydawnictwo Naukowe UAM Poznań, 2005)
The goal of this article is to unfold school media education curriculum in England and Germany. The author synthesizes basics of British and German media education programs. The author focuses on two different ways those countries took to input new and sometimes experimental teaching programs into schools. Both approaches are described in detail, and show clearly that there are many ways to teach people how to understand and use media for common good.
Media education in English and German curriculum